The P2X7 receptor antagonist Brilliant Blue G reduces serum human interferon‐γ in a humanized mouse model of graft‐versus‐host disease. (24th July 2017) - Geraghty, N. J.; Belfiore, L.; Ly, D.; Adhikary, S. R.; Fuller, S. J.; Varikatt, W.; Sanderson‐Smith, M. L.; Sluyter, V.; Alexander, S. I.; Sluyter, R.; Watson, D.
Summary: Graft‐ versus ‐host disease (GVHD) remains a major problem after allogeneic haematopoietic stem cell transplantation, a curative therapy for haematological malignancies. Previous studies have demonstrated a role for the adenosine triphosphate (ATP)‐gated P2X7 receptor channel in allogeneic mouse models of GVHD. In this study, injection of human peripheral blood mononuclear cells (PBMCs) into immunodeficient non‐obese diabetic‐severe combined immunodeficiency‐interleukin (NOD‐SCID‐IL)‐2Rγ null (NSG) mice established a humanized mouse model of GVHD. This model was used to study the effect of P2X7 blockade in this disease. From five weeks post‐PBMC injection, humanized mice exhibited clinical signs and histopathology characteristic of GVHD. The P2X7 antagonist, Brilliant Blue G (BBG), blocked ATP‐induced cation uptake into both murine and human cells in vitro . Injection of BBG (50 mg/kg) into NSG mice did not affect engraftment of human leucocytes (predominantly T cells), or the clinical score and survival of mice. In contrast, BBG injection reduced circulating human interferon (IFN)‐γ significantly, which was produced by human CD4 + and CD8 + T cells. BBG also reduced human T cell infiltration and apoptosis in target organs of GVHD. In conclusion, the P2X7 antagonist BBG reduced circulating IFN‐γ in a humanized mouse model of GVHD supporting a potential role for P2X7 to alter the pathology of this disease in humans. Abstract : Humanized mice injected with the P2X7 receptor antagonist Brilliant Blue G (BBG) demonstrate significantly reduced serum interferon gamma (IFN‐γ) compared to saline‐injected controls. IFN‐γ was produced by both human CD4+ and CD8+ T cells.